Diffusion-weighted MRI in the identification of renal parenchymal involvement in children with a first episode of febrile urinary tract infection - Anfigeno, Lorenzo; La Valle, Alberto; Castagnola, Elio; Verrina, Enrico Eugenio; Piaggio, Giorgio; Degl'Innocenti, Maria Ludovica; Piccotti, Emanuela; Wolfler, Andrea; Lembo, Francesca Maria; Bodria, Monica; Formigoni, Clelia; Boetto, Alice; et al. (Frontiers in Radiology, 2024)
Aims This study aims to assess the diagnostic accuracy of diffusion-weighted Magnetic Resonance Imaging (DW-MRI) and determine the inter-reader agreement between two expert radiologists in detecting pyelonephritic foci during the initial episode of febrile urinary tract infection (fUTI) in children aged 0–5 years. Also, we aim to establish the correlation between clinical data and DW-MRI findings. Methods Children aged 0–5 years presenting with their first episode of fUTI were included in the study and underwent DW-MRI and Ultrasound (US) examinations within 72 h of admission. Inter-observer agreement between the two expert radiologists in assessing DW-MRI scans was evaluated using Cohen's kappa statistic. Clinical and laboratory data were subjected to statistical analysis. Results 84 children (40 male, 44 female) with a mean age of 7.3 (SD 6.2) months were enrolled. DW-MRI detected pyelonephritis in 78 out of 84 cases (92.9%), with multiple foci observed in 73 out of 78 cases (93.6%). There was a “substantial” level of agreement between the two expert radiologists (κ = 0.725; observed agreement 95.2%). Renal US revealed pyelonephritis in 36 out of 78 cases (46.2%). White blood cell (WBC) count (p = 0.04) and lymphocyte count (p = 0.01) were significantly higher in patients with positive DW-MRI. Although not statistically significant, patients with positive DW-MRI had higher mean values of C-Reactive Protein, Procalcitonin, and neutrophil WBC count (7.72 mg/dl, 4.25 ng/dl, and 9,271 /μl, respectively). Conclusions DW-MRI exhibited excellent diagnostic performance in detecting pyelonephritic foci, with substantial inter-reader agreement among expert radiologists, indicating the reliability of the technique. However, a weak correlation was observed between laboratory parameters and DW-MRI results, potentially because of the low rate of negative DW-MRI findings.